Which trial do we need? A global, adaptive, platform trial to reduce death and disability from tuberculous meningitis - Thwaites, GE; Watson, J; Thuong, NTT; Huynh, J; Walker, T; Phu, NH (Elsevier, 2023)
Before the advent of anti-tuberculosis drugs in the 1940s, tuberculous meningitis (TBM) was a much-feared and almost universally fatal form of tuberculosis. Thus, when the first anti-tuberculosis drugs, streptomycin and para-aminosalycilic acid, became available, they were given first to those with TBM. Suddenly, the disease became treatable. Case fatality fell from 70% with streptomycin and para-aminosalycilic acid, to approximately 30% with the combination of isoniazid, pyrazinamide, and rifampicin.